Species delimitation in sharpnose sharks (genus Rhizoprionodon) in the western Atlantic Ocean using mitochondrial DNA - Mendonca, F. F. [UNESP]; Oliveira, C. [UNESP]; Burgess, G.; Coelho, R.; Piercy, A.; Gadig, Otto Bismarck Fazzano [UNESP]; Foresti, Fausto [UNESP] (Springer, 2011)
Despite Springer's (1964) revision of the sharpnose sharks (genus Rhizoprionodon), the taxonomic definition and ranges of Rhizoprionodon in the western Atlantic Ocean remains problematic. In particular, the distinction between Rhizoprionodon terraenovae and R. porosus, and the occurrence of R. terraenovae in South American waters are unresolved issues involving common and ecologically important species in need of fishery management in Caribbean and southwest Atlantic waters. In recent years, molecular markers have been used as efficient tools for the detection of cryptic species and to address controversial taxonomic issues. In this study 415 samples of the genus Rhizoprionodon captured in the western Atlantic Ocean from Florida to southern Brazil were examined for sequences of the COI gene and the D-loop and evaluated for nucleotide differences. The results on nucleotide composition, AMOVA tests, and relationship distances using Bayesian-likelihood method and haplotypes network, corroborates Springer's (1964) morphometric and meristic finding and provide strong evidence that supports consideration of R. terraenovae and R. porosus as distinct species.
Keywords: Conservation; Rhizoprionodon terraenovae; Rhizoprionodon porosus; Species delimitation; Elasmobranchs